Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd004907.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Package of care for active management in labour for reducing caesarean section rates in low-risk women

Abstract: Background Approximately 15% of women have caesarean sections (CS) and while the rate varies, the number is increasing in many countries. This is of concern because higher CS rates do not confer additional health gain but may adversely affect maternal health and have implications for future pregnancies. Active management of labour has been proposed as a means of reducing CS rates. This refers to a package of care including strict diagnosis of labour, routine amniotomy, oxytocin for slow progress and one to one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 39 publications
1
29
0
6
Order By: Relevance
“…As in MidU, four studies included in the Cochrane Review [7] found significant reduced rates of augmentation of labour in MLUs, but the remaining six showed no difference. Overall, meta-analyses do not show a significant difference in this outcome, with or without the addition of MidU data [6]. In the MidU study, induction of labour, PPH and low Apgar scores were not different between the two groups, in accord with the Cochrane Review findings.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…As in MidU, four studies included in the Cochrane Review [7] found significant reduced rates of augmentation of labour in MLUs, but the remaining six showed no difference. Overall, meta-analyses do not show a significant difference in this outcome, with or without the addition of MidU data [6]. In the MidU study, induction of labour, PPH and low Apgar scores were not different between the two groups, in accord with the Cochrane Review findings.…”
Section: Discussionmentioning
confidence: 62%
“…Certainly, early routine ARM, one facet of AML, has been criticised as "not scientifically justified" [4] and a Cochrane Review found "no shortening of the length of first stage of labour and a possible increase in caesarean section", concluding "routine amniotomy is not recommended for normally progressing labours or in labours which have become prolonged" [5]. Another Cochrane Review found that AML was associated with a small decrease in caesarean section (CS), but that it was "highly prescriptive and interventional" [6] and the authors advised further research to determine the acceptability of AML to women [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Augmentation of labour is the process of uterine stimulation using intravenous oxytocin infusion to increase frequency, duration and intensity of contractions after the onset of spontaneous labour. It is used to treat delayed labour when uterine contractions are not strong or coordinated enough to cause cervical dilatation [4]. Labour augmentation aims to shorten labour so prevent complications related to prolonged labour.…”
Section: Introductionmentioning
confidence: 99%
“…A simple example of how the process of situating constructs the obstetric situation could make use of the concept of active management of labour [59]. Here, midwifes are instructed not to accept patients to the delivery unit unless they are in active labour.…”
Section: Discussionmentioning
confidence: 99%